2023
DOI: 10.1186/s13000-023-01368-y
|View full text |Cite
|
Sign up to set email alerts
|

Reticular fibre structure in the differential diagnosis of parathyroid neoplasms

Abstract: Background To investigate the characteristics of reticular fibre structure (RFS) in parathyroid adenoma (PTA), atypical parathyroid tumour (APT), and parathyroid carcinoma (PTC), and to assess its value as a diagnostic indicator. Methods Clinical data and pathological specimens of patients with PTA, APT or PTC were collected. Reticular fibre staining was performed to observe the characteristics of RFS. This study evaluated the incidence of RFS dest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The signi cance of reticular ber staining in diagnosing parathyroid tumors, adrenocortical adenomas, and pituitary adenomas is well-established [21][22]. Reticular bers, challenging to discern under H&E staining, become readily observable post-immersion in a silver ammonia solution and subsequent reduction with formaldehyde, yielding a black color.…”
Section: Discussionmentioning
confidence: 99%
“…The signi cance of reticular ber staining in diagnosing parathyroid tumors, adrenocortical adenomas, and pituitary adenomas is well-established [21][22]. Reticular bers, challenging to discern under H&E staining, become readily observable post-immersion in a silver ammonia solution and subsequent reduction with formaldehyde, yielding a black color.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a small number of sparse reticular fibers around the tumor cancer nest with good differentiation and low malignancy, or no reticular fibers. In contrast, poorly differentiated and aggressive tumor nests can be surrounded by abundant, dense reticular fibers [ 39 ]. It has also been suggested that the perivascular fibrostroma favors tumor invasion and dissemination [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of reticular fiber staining in diagnosing parathyroid tumors, adrenocortical adenomas, and pituitary adenomas is well-established [ 31 , 32 ]. Reticular fibers, challenging to discern under H&E staining, become readily observable post-immersion in a silver ammonia solution and subsequent reduction with formaldehyde, yielding a black color.…”
Section: Discussionmentioning
confidence: 99%